Adapting the Short Grit Scale with Exploratory Structural Equation Modeling for Portuguese College Students. Issue 5 (October 2022) - Frontini, Roberta; Monteiro, Diogo; Rodrigues, Filipe; Matos, Rui; Antunes, Raúl
The Short Grit Scale (Grit–S) is a self- and informant-report version of the longer Grit Scale, and it retains the 2-factor structure of the original scale. Our purpose in this research was to measure trait-level perseverance and passion for long-term goals by translating and validating the Grit-S for Portuguese respondents. Our participants were 572 college students (135 female, 437 male; age range 18–30 years, M age = 21.47, SD = 2.29 years) from twelve Portuguese universities. Our data confirmed the scale's two-factor structure ("consistency of interests" and "perseverance of effort") and demonstrated appropriate adjustment values (CFI = 0.999, TLI = 0.981, SRMR = 0.017, RMSEA = 0.001, CI90%= 0.000–0.041). We found the adapted scale to be invariant for sex. Use of the scale confirmed an association between grit and well-being. These results imply that other investigators and practitioners interested in this scale may now apply it with Portuguese young adults.